Optimasi Kadar Abu pada Campuran Biochar dengan Pupuk NPK Melalui Metode Coating - Deri , Adrianus; Iskandar , Taufik; Abrina Anggraini, Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2020)
Improvement of decreased soil quality and to maintain available nutrients for a long time in the soil can be achieved by applying balanced fertilization and the use of soil amendments such as biochar. NPK Element N plays a role in helping the adequacy of green leaves for photosynthesis and stimulating plant growth and helping to form organic compounds that plants need. The P element serves to stimulate root growth and accelerate the plant process in the generative and flowering stages. K will help the plant to be stronger and sturdier, providing resistance to disease and drought. The process of this research begins with biochar, initially, 5 kg of rice husk biochar is finely ground and sifted at 75 mesh size to mix with NPK. Weighing 100 gr of biochar, then mixing 100 gr of biochar with NPK (grams): 10, 20, 30. Make a coating mixture and water (water and starch). The mixing time was 15 minutes. The coated Biochar was granulated and dried in an oven at 105oC for 1 hour. Analyzed coating results: Dustiness. Statistical analysis using SPSS. The lowest ash content possessed by biochar is at a 30% NPK concentration with a 30% starch coating concentration of 0.0609%. Good quality is found at a concentration of 10% NPK and 30% starch coating. This is because it is influenced by the value of the proximate analysis where the low ash content and the high dissolving time and the percentage of the coating produced.